Analisis Pengukuran Kinerja Perbankan Syariah dengan Menggunakan Metode Angels (Studi Kasus pada Bank Syariah Indonesia KCP. Medan Ringroad) - Kurniawati, Endang; Imsar; Harahap, Rahmat Daim (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
In assessing the performance of Islamic banks, it is not only seen from their financial reports, but also based on the concept of IMAN (Islamic values-based performance assessment), which is the embodiment of the Islamic values dimensions, namely: ibadah (worship), muamalah (transactions), amanah (trustworthiness), and ihsan (excellence). The assessment system for the health of Islamic banks referred to here is ANGELS. ANGELS is an acronym for Amanah management, non-economic wealth, Give out, Earnings, Capital and assets, Liquidity and sensitivity to market, and socio-economic wealth. Each factor of ANGELS is part of the